Komunikasi Antarbudaya Masyarakat Multikultur dalam Menciptakan Toleransi - Riswanto Riswanto (JOPPAS: Journal of Public Policy and Administration Silampari, 2022)
The purpose of this study was to find out how intercultural communication creates tolerance in the people of the Permu Immigration Village, where the Permu Immigration Village has ethnicities with five different multiculturalities that can maintain a tolerant life. The research method used is a qualitative research method by relying on Face Negotiation Theory to see the interaction behavior of people of different ethnicities with facework in order to see communicative behavior. The results of this study indicate that interactions between ethnic immigrants and indigenous ethnicities have taken place in the Permu Immigration Village, which has always avoided prolonged conflict and has become a tolerant village. mutual respect and respect for the existence of agreement decisions that have existed since long ago there has never been any change to the agreement. The conclusion of the research is that multiculturalism in the Permu Immigration Village applies negotiation theory and an attitude of obliging (obligation) towards agreements and in avoiding problems so that they are not prolonged. Keywords: Builds, Comunication, Harmonization, Intercultural, Multiculture